The effect of an empowerment program on knowledge and cancer cervical screening participation among reproductive age women in Indonesia: A randomized clinical trial - Nofa Anggraini; Susi Susanti; Rima Akhiri; Sisi Amelia; Dewi Cahyani (Faculty of Nursing Universitas Padjadjaran, 2025)
Background: Cervical cancer in Indonesia is the second leading cause of death and a significant health burden, largely due to low screening coverage. Indonesia faces challenges in developing women's health due to a lack of information, studies, weak relationship between research, management, planning, and service provision, and limited resources and expertise. This study aimed to examine the effect of an empowerment-based educational intervention on improving knowledge and participation in cervical cancer screening among women of reproductive age in Indonesia. Methods: A randomized clinical trial was conducted in Jakarta, Indonesia, from February to July 2023, involving 150 eligible women. Participants were allocated to intervention or control groups using block randomization (block size = 4) with a 1:1 ratio. The intervention group received a three-week empowerment program consisting of six educational sessions. Outcomes, including cervical cancer knowledge and screening participation, were measured at baseline and eight weeks post-intervention. Data were analyzed using t-tests, chi-square tests, and linear regression. Risk ratios and differences were estimated using marginal standardization. Analyses followed the intention-to-treat principle, with blinding applied during data analysis. Results: A randomized study with 80 participants showed an improvement in knowledge about cervical cancer and cancer cervical screening participation at 8 weeks. The intervention group showed a mean difference of 3.91 (1.38) and 4.24 (0.45) p<0.05. More participants in the intervention group reached Minimal Clinically Important Differences (MCIDs) in knowledge about cervical cancer and cancer cervical screening participation than in the control group, with a relative risk of 2.34 (95% CI=1.08-4.36) and 2.57 (95% CI=1.21-4.90), respectively. Conclusion: An empowerment program significantly enhances knowledge and participation in cancer cervical screening among reproductive age women in Indonesia after intervention, but further studies are needed to determine its long-term impact.